Physiological and skeletal morphological responses of corals to light limitation in turbid environments - Teo, Bryan Jun-kai (Nanyang Technological University, 2024)
This study aims to investigate the physiological and morphological responses of corals in turbid reef environments. Coral fragments were harvested via recreational SCUBA methods from light-exposed areas of coral colonies. The samples were blasted using an airbrush to collect tissue and symbiont in a mixture with seawater, after which the skeletons were bleached and dried to measure bulk skeletal density. The dried skeletons were also placed on a light scanner to produce a 3D model to provide surface area, volume, corallite width and corallite density measurements. Tissue biomass was quantified using Loss-on-Ignition (LOI) method while symbiont density was measured using a haemocytometer. When comparing bulk skeletal densities of turbid corals to literature values from less turbid environments, the skeletal densities of turbid corals were lower than those from less turbid environments, likely due to resource-partitioning strategies. Mean skeletal densities and biomass increased in the following order according to growth morphology: massive, plate then branching. The trend could be explained by the efficiency of the different growth forms in dispersing sediment load-induced mechanical stress. Morphological features such as surface area to volume (S/V) ratio, corallite width and corallite density could also be used to predict the trophic mode of different corals, with autotrophs having lower S/V ratios, corallite densities and smaller corallite widths while heterotrophs show the opposite trend. Future studies could involve isotopic analysis and symbiont sequencing could expand our knowledge of resource acquisition strategies of corals in turbid reefs.